Study on measles antibody status in children below nine months of age and its implication on measles vaccination - Chowdhury, Jamal Pasha; Mondol, Md Eunus Ali; Uddin, Muhammad Jalal; Hoque, Md Monirul; Kawser, Narjis Maliha; Rahim, Ina; Wadud, ABM Abdul (Journal of Armed Forces Medical College, Bangladesh, 2009)
doi:10.3329/jafmc.v4i2.1820 JAFMC Bangladesh Vol.4(2) 2008 5-9